Environmental management of the water supply of Cidade Universitária Prof. José da Silveira Netto (UFPA) and implementation model for granting water use (Research, Society and Development, 2023)
This study was carried out at Cidade Universitária Prof. José da Silveira Netto, from the main campus of the Federal University of Pará (UFPA), on the assessment of the environmental management of water supply and the current situation of regularity regarding the model for granting the right to use water resources in the administrative body, the Secretariat of State of the Environment and Sustainable Development (SEMAS/PA). The objective of the study is to propose the procedures necessary for the implementation of a project to support good environmental management of urban sanitation systems, based on Normative Instruction nº. 3 of March 26, 2014 SEMAS/PA. The methodology was developed through documentary/bibliographical research and the competent bodies (SEMAS/PA, CPRM and FEMAC) and technical visits to sectors of the university city. Studies show that the process of environmental management of water resources and the water rights and concession model need to be improved from the beginning. Use of water resources on the main campus of the Federal University of Pará to meet this requirement and comply with applicable regulations and any technical conditions proposed by the competent environmental protection body.